Analyzing the Effects of Psychotherapy on Weight Loss after Laparoscopic Gastric Bypass or Laparoscopic Adjustable Gastric Banding in Patients with Borderline Personality Disorder: A Prospective Study. (December 2017) - Gallé, F.; Cirella, A.; Salzano, A. M.; Onofrio, V. Di; Belfiore, P.; Liguori, G.
Background and Aims: Personality disorders are frequently associated with eating disorders in obese patients and may negatively affect weight loss and maintenance after bariatric surgery. This non-randomized study aimed to assess the effects of different psychotherapeutic interventions on weight loss in a sample of patients with borderline personality disorder who underwent laparoscopic gastric bypass or laparoscopic adjustable gastric banding. Materials and Methods: A total of 153 bariatric patients meeting borderline personality disorder criteria were chosen voluntarily and consecutively to undergo an interpersonal individual treatment (n = 50), a dialectical behavioral group treatment (n = 50), or treatment as usual (n = 53) for a year after surgery. Their body mass index was measured before and at the end of each treatment. Results and Conclusion: A total of 12 patients (7.8%) dropped out of the study. Significantly higher body mass index reductions were registered in both experimental groups (−14.2 and −9.4 kg/m 2, respectively) compared with the treatment as usual group (−2.1 kg/m 2 ; p < 0.01). Treated patients who underwent laparoscopic gastric bypass (total n = 94) showed better outcomes than those who underwent laparoscopic adjustable gastric banding (total n = 45), while no differences were observed in untreated patients. This study demonstrates the role of pre-operative psychological assessment and post-operative psychotherapeutic support in improving weight loss among bariatric patients with borderline personality disorder. A randomized controlled trial is needed to confirm these preliminary findings.